Association of Personal Characteristics and Effectiveness of Immunotherapy in Late-Stage Non-Small Cell Lung Cancer: A Systematic Review. Issue 2 (17th February 2022) - Patel, Krishna; Alpert, Naomi; Tuminello, Stephanie; Taioli, Emanuela
Abstract: Background: Although immunotherapy can increase survival in non-small cell lung cancer (NSCLC), response rates are low. It is unclear which characteristics contribute to variability in immunotherapy efficacy and survival. Research is needed to identify reasons for heterogeneity in response rates to better tailor treatments. Methods: Web of Science, Ovid EMBASE, and MEDLINE were queried from 2013 to January 2021, and all studies reporting overall or progression-free survival for patients treated with immunotherapy for NSCLC of at least stage IIIB were screened. Results: Included were 18 randomized controlled trials (RCTs; 6534 immunotherapy RCTs; 11 192 nonimmunotherapy RCTs) and 16 observational studies (n = 9073 immunotherapy patients). Among RCTs, there was improved survival with the addition of immunotherapy in patients aged younger than 65 years in 10 of 17 studies; smokers in 8 of 15 studies; and males in 10 of 17 studies and 6 of 17 females. Only 5 studies reported outcomes by race. Among observational studies, younger patients (aged younger than 60, younger than 65, or younger than 70 years in most studies) had better survival than older patients (aged 60 years and older, 65 years and older, or 70 years and older) in 4 of 13 studies, ever-smokers in 7 of 13, and females in 2 of 14. Three studies reported race with mixed results. Conclusion: Although evidence is mixed, younger patients, smokers, and males may derive more benefit from immunotherapy. Evidence on racial differences is limited. Physicians should be mindful of personal characteristics when formulating treatment plans. Further research is needed to understand underlying mechanisms and to identify the best immunotherapy candidates and alternative treatments for those unlikely to benefit.